Ocular ketoconazole-loaded proniosomal gels: formulation, ex vivo corneal permeation and in vivo studies - Ghada A. Abdelbary; Maha M. Amin; Mohamed Y. Zakaria (Taylor & Francis Group, 2017)
Context: Vesicular drug carriers for ocular delivery have gained a real potential. Proniosomal gels as ocular drug carriers have been proven to be an effective way to improve bioavailability and patient compliance. Objective: Formulation and in vitro/ex vivo/in vivo characterization of ketoconazole (KET)-loaded proniosomal gels for the treatment of ocular keratitis. Materials and methods: The effect of formulation variables; HLB value, type and concentration of non-ionic surfactants (Tweens, Spans, Brijs and Pluronics) with or without lecithin on the entrapment efficiency (EE%), vesicle size and in vitro KET release was evaluated. An ex vivo corneal permeation study to determine the level of KET in the external eye tissue of albino rabbits and an in vivo assessment of the level of KET in the aqueous humors were performed. Results and discussion: In vivo evaluation showed an increase in bioavailability up to 20-folds from the optimum KET proniosomal gel formula in the aqueous humor compared to drug suspension (KET-SP). The selected formulae were composed of spans being hydrophobic suggesting the potential use of a more hydrophobic surfactant as Span during the formulation of formulae. Factors that stabilize the vesicle membrane and increase the entrapment efficiency of KET (namely low HLB, long alkyl chain, high phase transition temperature) slowed down the release profile. Conclusions: Proniosomal gels as drug delivery carriers were proven to be a promising approach to increase corneal contact and permeation as well as retention time in the eye resulting in a sustained action and enhanced bioavailability.